PENGARUH PENERAPAN MODEL KOOPERATIF MAKE A MATCH PADA MATA PELAJARAN IPA KELAS V TERHADAP MINAT BELAJAR SISWA DI SDN TANJUNG DUREN SELATAN 05 - Ayu Indriyani; Harlinda Syofyan (STKIP Subang, 2023)
This research aims to know the effect of applying cooperative model learning kind of make a match to the student's level of interest in learning the science of nature.Method in this study uses a method with a quarantinative approach, This research uses numbers as data.Method used survey method, with data collecting techniques using questionnaires or rockets.The sample in this study is a class v. A consisting of 30 students.This study was conducted on June 13, 2013.This research uses tests in determining research hypothesis, By calculations it's got a count of 4,938.So that it can be written 4,938 (count ) > 2,048 (ttabel ) with significant 0,001 < 0.05.It can therefore be concluded that h0 is rejected and h1 is accepted which means there's a positive influence between the model defense jarn make a match with the student's study interests.